Moral injury after abortion: exploring the psychospiritual impact on Catholic women - Carleton, Tara C. (Routledge, 2023)
"Moral Injury After Abortion delves deeply into the psychospiritual responses that some women experience when an abortive act conflicts with their moral beliefs and values. The book is grounded in a qualitative, phenomenological study that examined the lived experiences of 30 Christian women post-abortion. The study participants' voices are woven throughout the book in a way that offers the reader a narrative understanding of their experiences and a thick description of the psychospiritual impact of moral injury after abortion. The book provides mental health scholars and professionals with strategies for assessing for moral injury experiences among women post-abortion as well as a guide for addressing the spiritual and psychological impact of post-abortive moral injury"--